A Novel Peptide Antibiotic Produced by Streptomyces roseoflavus Strain INA-Ac-5812 With Directed Activity Against Gram-Positive Bacteria - Vasilchenko, Alexey S.; Julian, William T.; Lapchinskaya, Olda A.; Katrukha, Genrikh S.; Sadykova, Vera S.; Rogozhin, Eugene A. (Frontiers in Microbiology, 2020)
In this work, we report the isolation and detailed functional characterization for the new non-ribosomally synthesized antibiotic 5812-A/C, which was derived from metabolites of Streptomyces roseoflavus INA-Ac-5812. According to its chemical structure the studied 5812-A/C preliminary is composed of a cyclic peptide part covalently bounded with an arabinose residue. N-terminal amino acid sequencing of the native peptide has identified its partial structure of Leu-Asp-Gly-Ser-Gly and consisting of a Tyr residue that it supposed two-component peptide nature for the molecule studied. However, the structural analysis of the antibiotic complex derived from Streptomyces roseoflavus INA-Ac-5812 is still ongoing. The mechanism of action of 5812-A/C was assessed in comparison with its most related analogue, the lipopeptide antibiotic daptomycin, given the presence in both antimicrobials of an L-kynurenine amino acid residue. The inhibitory activity of 5812-A/C against Gram-positive bacteria including methicillin-resistant strains of S. aureus was similar to daptomycin. The mechanism of action of 5812-A/C was associated with the disruption of membrane integrity, which differs in comparison to daptomycin and is most similar to the antimicrobial membrane-disturbing peptides. However, 5812-A/C demonstrated a calcium-dependent mode of action. In addition, unlike daptomycin, 5812-A/C was able to penetrate mature biofilms and inhibit the metabolic activity of embedded S. aureus cells. At the same time, 5812-A/C has no hemolytic activity toward erythrocyte but possessed weak cytotoxic activity represented by heterochromatin condensation in human buccal epithelium cells. The biological properties of the peptide 5812-A/C suggest its classification as a calcium-dependent antibiotic effective against a wide spectrum of Gram-positive pathogenic bacteria.